Ryōsai Kenbo: Domestikasi Perempuan dan Pembentukan Negara Bangsa dalam Era Meiji Jepang - Nisia Nur Dwi Agusta; Tribuana Tungga Dewi (IZUMI, 2025)
During the Meiji era, Japan undertook rapid modernization to compete with Western powers. One of the cultural strategies employed by the government was the promotion of the ryōsai kenbo ideology—“good wife, wise mother”—to shape ideal women as domestic supporters of national progress. This study explores the development of ryōsai kenbo as a state policy in women's education, from the Charter Oath of 1868 and the Iwakura Mission to the Imperial Rescript on Education (1890) and the Girls' High School Order (1899). Using a qualitative historical approach, the research analyzes how ryōsai kenbo reflected Japan’s effort to establish a functional and harmonious society, as explained through Talcott Parsons’ structural-functional theory. Findings show that although the ideology confined women to domestic roles, it simultaneously legitimized women’s access to education and redefined their societal significance. Rather than viewing ryōsai kenbo solely as a tool of subjugation, this article argues it was a strategic effort to construct a cohesive national identity through clearly defined gender roles. Thus, the ideology served both as a means of female domestication and a pillar of Japan’s modernization agenda. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor